Diffusion of Lambda(c) in hot hadronic medium and its impact on Lambda(c)/D ratio - Ghosh, Sabyasachi [UNESP]; Das, Santosh K.; Greco, Vincenzo; Sarkar, Sourav; Alam, Jan-e (Amer Physical Soc, 2014)
The drag and diffusion coefficients of the Lambda(c)(2286 MeV) have been evaluated in the hadronic medium which is expected to be formed in the later stages of the evolving fireball produced in heavy ion collisions at RHIC and LHC energies. The interactions between the Lambda(c) and the hadrons in the medium have been derived from an effective hadronic Lagrangian, as well as from the scattering lengths obtained in the framework of heavy baryon chiral perturbation theory (HB chi PT). In both the approaches, the magnitude of the transport coefficients turn out to be significant. A larger value is obtained in the former approach with respect to the latter. Significant values of the coefficients indicate a substantial amount of interaction of the Lambda(c) with the hadronic thermal bath. Furthermore, the transport coefficients of the Lambda(c) are found to be different from the transport coefficients of the D meson. The present study indicates that the hadronic medium has a significant impact on the Lambda(c)/D ratio in heavy ion collisions.